An analysis of topics and vocabulary in Chinese oral narratives by normal speakers and speakers with fluent aphasia. (2nd January 2018) - Law, Sam-Po; Kong, Anthony Pak-Hin; Lai, Christy
ABSTRACT: This study analysed the topic and vocabulary of Chinese speakers based on language samples of personal recounts in a large spoken Chinese database recently made available in the public domain, i.e. Cantonese AphasiaBank (http://www.speech.hku.hk/caphbank/search/ ). The goal of the analysis is to offer clinicians a rich source for selecting ecologically valid training materials for rehabilitating Chinese-speaking people with aphasia (PWA) in the design and planning of culturally and linguistically appropriate treatments. Discourse production of 65 Chinese-speaking PWA of fluent types (henceforth, PWFA) and their non-aphasic controls narrating an important event in their life were extracted from Cantonese AphasiaBank. Analyses of topics and vocabularies in terms of part-of-speech, word frequency, lexical semantics, and diversity were conducted. There was significant overlap in topics between the two groups. While the vocabulary was larger for controls than that of PWFA as expected, they were similar in distribution across parts-of-speech, frequency of occurrence, and the ratio of concrete to abstract items in major open word classes. Moreover, proportionately more different verbs than nouns were employed at the individual level for both speaker groups. The findings provide important implications for guiding directions of aphasia rehabilitation not only of fluent but also non-fluent Chinese aphasic speakers.